Exploring Formative Feedback in Virtual Primary Education: Towards a Conceptual Structure - Garcia castro, Raul; Perochena Moran, Roxana Rita; Llapa Medina , Martín Pedro (International Electronic Journal of Elementary Education, 2026)
Formative feedback is a key resource for promoting learning among primary school students. In virtual environments, it gains greater relevance as it intervenes at different stages of the educational process, highlighting the need to understand how teachers perceive it, apply it, and which factors condition their pedagogical practice. The objective of this study was to understand how primary school teachers conceive and implement formative feedback in virtual contexts and, on that basis, to develop a conceptual structure that synthesizes their experiences. A qualitative exploratory approach was adopted, grounded in grounded theory, which included semi-structured interviews with 65 teachers from 15 educational institutions in the Tacna region of Peru. Data analysis was supported by Atlas.ti 23 software and involved the identification of emerging categories through open, axial, and selective coding processes. The findings indicate that teachers understand feedback as a comprehensive pedagogical process oriented toward formative assessment, progressive improvement of learning, capacity development, and student-centered support. The study also identified that strategies perceived as more effective were those related to interactive and personalized use of diverse resources, whereas less effective strategies were linked to approaches primarily focused on grading. In conclusion, a conceptual structure of virtual formative feedback is proposed, which articulates cognitive, socio-emotional, and techno-pedagogical dimensions. This structure also describes the factors that influence feedback, its types, the purposes attributed by teachers, and the student-centered approach. The study contributes both to the foundations of pedagogical practice and to future research in primary education.